Preparation, forming and evaluation method of renewable H2S adsorption material
The renewable adsorption H2S material prepared and formed by hydrothermal synthesis has solved the problem that H2S adsorbent materials cannot achieve renewable adsorption in the prior art, and achieved renewable adsorption and desorption at room temperature or low temperature, which is highly efficient, energy-saving and chemical Stable characteristics.
Patent Information
- Application Number
- CN202411446344.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to realize the renewability of H2S adsorbent materials, and low-temperature regeneration is prone to produce elemental sulfur, while high-temperature easily destroys the structure of the adsorbent materials.
By hydrothermal synthesis, scandium trifluoric acid reacts with biphenyltetracarboxylic acid to prepare a renewable adsorption H2S material, and is molded through the binder PVA to achieve renewable adsorption and desorption at room temperature or low temperature.
Renewable adsorption of H2S is achieved, and the material structure damage is avoided due to high temperature desorption. It has chemical stability and large porosity, high adsorption capacity and energy-saving and efficient.
Smart Images

Figure CN119406382A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorption materials, and in particular to a renewable hydrogen sulfide adsorption material, specifically to a preparation, molding and evaluation method of the renewable H2S adsorption material. Background Art
[0002] Hydrogen sulfide (H2S) is a colorless gas that is highly corrosive, flammable, and a toxic chemical. It is also a major air pollutant that forms acid rain and is poisonous to humans, causing serious neurological disorders. At low concentrations (10 ppm), hydrogen sulfide can cause fatigue and headaches, and then irritate the eyes, nose, and throat. Hydrogen sulfide was also used by the United Kingdom as a chemical warfare agent (CWA) in 1916.
[0003] In the field of protection, the existing technology for protecting against such toxic gases in the air is mainly achieved by impregnating activated carbon with metal oxides and TEDA. This kind of carbon impregnated with chemical substances is used in air purification systems. Due to the limitation of adsorption capacity, the impregnated carbon needs to be replaced, and the impregnated carbon adsorbed by H2S is not renewable, which consumes resources and funds and may cause environmental pollution. In addition, due to the strong polarity of H2S and the production of elemental sulfur, the current research on renewable protection of H2S is technically difficult and rarely reported in the existing technology.
[0004] Therefore, it is urgent to develop a new adsorption material with H2S adsorption function and renewability to replace the current adsorption material mainly based on impregnated carbon in air purification systems, and provide technical support for renewable air purification system materials.
[0005] For many years, other industries have considered using physical and chemical processes to remove hydrogen sulfide. For example, alkanolamine solutions are used to chemically absorb hydrogen sulfide, but they have disadvantages such as low hydrogen sulfide capture rate, pipeline corrosion, high operating costs, and complex recovery rates. At present, new technologies that use porous solid materials to effectively remove hydrogen sulfide through adsorption processes have developed rapidly. For example, Melo and colleagues studied the capture of hydrogen sulfide by zeolite 13X under ambient conditions. After hydrogen sulfide adsorption, an irreversible chemical adsorption process occurs, and regenerative adsorption and desorption cannot be achieved. It needs to be heated to above 450°C to achieve high-energy regeneration, but the structure of the adsorbent material is easily destroyed at this temperature. Bordiga et al. studied the regenerative adsorption performance of MOF-74 (Ni) for hydrogen sulfide and found that MOF-74 (Ni) has a very strong interaction with H2S, producing irreversible metal-sulfur bonds, and the analytical process requirements are very high. Summary of the invention
[0006] In order to solve the problems that the existing H2S air purification adsorption materials cannot be regenerated after adsorption, the low-temperature regeneration in the prior art is prone to produce elemental sulfur and cannot be realized, and high temperature easily destroys the structure of the adsorption material, the present invention provides a preparation, molding and evaluation method for a regenerable H2S adsorption material.
[0007] The present invention is implemented by the following technologies: The present invention provides a method for preparing a regenerable H2S adsorbing material, comprising the following steps: a. Take 0.06~0.08mmol of scandium trifluoride solid and 0.010~0.03g of biphenyltetracarboxylic acid (H4BPTC) and place them in a polytetrafluoroethylene hydrothermal reactor, add 4.0~5.0mL of tetrahydrofuran solution, 3.0~5.0mL of N,N-dimethylformamide solution, 1.0~2.0ml of water, and 2~3 drops of 36.5% hydrochloric acid, and ultrasonicate for 15min to make the mixture solution evenly dispersed to obtain a mixed solution.
[0008] b. Place the mixed solution in a tetrafluoroethylene hydrothermal reactor, tighten the hydrothermal reactor, place it in an oven, and react the mixed solution at 75°C for 72 hours.
[0009] c. After cooling to room temperature, filter and separate the colorless crystalline product, wash it with acetone 2 to 3 times, and dry it at 65°C to synthesize the H2S regenerable adsorption material.
[0010] The present invention provides a method for forming a regenerable H2S adsorbing material, comprising the following steps: a. Dissolve a binder in water to obtain a binder solution; further, the binder is a polyvinyl alcohol solid; specifically, take a polyvinyl alcohol solid (PVA), dissolve it in 100 mL of hot water, and stir until it becomes a transparent liquid to obtain a polyvinyl alcohol solution.
[0011] b. Mix the synthesized H2S regenerable adsorbent material with methyl cellulose solid, add it into 0.5% binder solution, i.e. polyvinyl alcohol solution, and mix and stir.
[0012] c. Put the mixture with the binder into an extruder for extrusion molding. Then, dry the extruded material at room temperature for 8 hours and then dry it in an oven at 105°C for 3 hours to obtain a molded adsorption material.
[0013] The present invention provides an evaluation method for a regenerative H2S adsorbing material. The evaluation device for evaluating the regenerative H2S adsorbing material has the following structure: comprising an adsorption device and a desorption device connected to the same stainless steel measuring tube, the adsorption device comprising a compressed air filter, the first pipeline of the compressed air filter being connected to the inlet of a drying tower, the outlet of the drying tower being connected to a poison gas cylinder through a third pipeline, the third pipeline being connected to a first orifice plate flowmeter, and the poison gas cylinder being connected to an inlet of a mixing ball; The second pipeline of the compressed air filter is connected to the humidity regulator, and multiple groups of humidity regulators are connected in parallel to achieve the effect of humidity control. The humidity regulator is connected to another inlet of the mixing ball through the fourth pipeline, and the fourth pipeline is connected to the dry-bulb thermometer and the second orifice flowmeter in sequence; the outlet of the mixing ball is connected to the inlet of the stainless steel measuring tube through the fifth pipeline, and the third orifice flowmeter is connected to the fifth pipeline. The stainless steel measuring tube is filled with a molded adsorption material, and the outlet of the stainless steel measuring tube is connected to the indicator box; The desorption device comprises a stainless steel measuring tube arranged in a water bath, two ends of the stainless steel measuring tube are respectively connected to an air generator and a vacuum pump, and a mass flow meter is installed on the pipeline connecting the stainless steel measuring tube and the air generator.
[0014] The evaluation method is carried out using the above evaluation device, relying on the principles of pressure swing adsorption (PSA) and temperature swing adsorption (TSA), and includes the following steps: a. Place the formed adsorbent material in a stainless steel measuring tube of an adsorption device and perform adsorption treatment on the adsorbent material, i.e., the adsorbate enters the stainless steel measuring tube filled with adsorbent and is adsorbed at room temperature and pressure. When the indicator in the indicator box changes color, i.e., when it penetrates, record and calculate the H2S adsorption capacity; Specifically include: aa, compressed air enters the humidity regulator from the compressed air filter, and after the temperature and flow are monitored by the dry-bulb thermometer and orifice flowmeter, it enters the mixing ball and mixes with the H2S in the gas bottle that enters the mixing ball.
[0015] ab, the mixed poison gas enters the stainless steel measuring tube from the mixing ball and passes through the adsorption material.
[0016] ac, the progress of contamination is judged by the color change of the indicator in the indicator box connected to the rear of the stainless steel measuring tube, the flow rate is recorded by the third orifice flowmeter installed between the mixing ball and the stainless steel measuring tube, and the H2S adsorption capacity is calculated based on the flow rate and time.
[0017] b. When the poison changes the color of the indicator in the indicator box, it means that the poison penetrates the adsorption material and removes the stainless steel measuring tube.
[0018] c. Connect the stainless steel measuring tube to the desorption device, connect an air generator and a vacuum pump to both sides of the stainless steel measuring tube respectively, place the stainless steel measuring tube in a water bath at 60℃~70℃, and introduce air at a flow rate of 200mL / min into the stainless steel measuring tube to vacuum desorb the adsorbent material. At the same time, clean hot air is used for desorption to remove H2S from the system in the formed adsorption material, so as to achieve the purpose of regeneration. The desorption time is the same as the adsorption time. In the actual operation process, adsorption and desorption need to be started at the same time. After one column is saturated with adsorption, another column is used for adsorption, and at the same time, the column starts to desorb. Therefore, when studying the material, it is necessary to ensure that the adsorption and desorption times are the same for desorption tests.
[0019] d. After desorption is completed, the stainless steel measuring tube is placed in the evaluation device for adsorption, and the evaluation steps a to c are repeated. The prepared adsorption material is evaluated through multiple cycles of adsorption-desorption experiments. The whole process is strictly carried out in a fume hood and a gas mask is worn.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a preparation, molding and evaluation method of a renewable H2S adsorption material. The material is synthesized from trifluoromethyl scandium and biphenyltetracarboxylic acid by a hydrothermal synthesis method. The molding process is simple, green and energy-saving. The process steps used are simple and the materials used are cheap. The material is molded by a binder PVA to prepare a renewable H2S adsorption material. The adsorbent can realize regenerative adsorption and desorption at room temperature or low temperature, does not require a high desorption temperature, is energy-saving and efficient, has chemical stability and a relatively large porosity, and the adsorption material has a high adsorption capacity and contains relatively weak adsorption sites. The adsorption effect of the weak adsorption sites is beneficial to realizing the renewable adsorption of H2S at room temperature.
[0021] Based on the principles of pressure swing adsorption (PSA) and temperature swing adsorption (TSA), the material was evaluated for adsorption and desorption through an evaluation device. The evaluation device is simple to operate and has strong practicability. It verifies that the material has regenerative adsorption performance and can achieve regenerative adsorption of H2S. The obtained data provide corresponding operating parameters for H2S regenerative adsorption materials and devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the structure of the adsorption device of the present invention.
[0023] Figure 2 It is a schematic diagram of the structure of the desorption device of the present invention.
[0024] Figure 3 It is a schematic diagram of the structure of the adsorption device of the present invention.
[0025] In the figure: 1-compressed air filter, 2-humidity regulator, 3-dry and wet bulb thermometer, 4-second orifice flowmeter, 5-mixing ball, 6-poison gas cylinder, 7-drying tower, 8-stainless steel measuring tube, 9-indicator box, 10-first orifice flowmeter, 11-third orifice flowmeter, 12-water bath, 13-air generator, 14-vacuum pump, 15-mass flowmeter;
[0026] L1-first pipeline, L2-second pipeline, L3-third pipeline, L4-fourth pipeline, L5-fifth pipeline DETAILED DESCRIPTION
[0027] The specific embodiments of the present invention are described below in conjunction with the accompanying drawings.
[0028] The present invention provides a method for preparing a regenerable H2S adsorbing material, comprising the following steps: a. Take 0.061 mmol of scandium trifluoride solid and 0.010 g of biphenyltetracarboxylic acid and place them in a polytetrafluoroethylene hydrothermal reactor, add 4.0 mL of tetrahydrofuran solution, 3.0 mL of N,N-dimethylformamide solution, 1.0 ml of water, and 2 drops of 36.5% hydrochloric acid, and ultrasonicate for 15 minutes to make the mixture solution evenly dispersed to obtain a mixed solution.
[0029] b. Place the mixed solution in a PTFE hydrothermal reactor, tighten the hydrothermal reactor, and place it in a 75°C oven to react for 72 hours.
[0030] c. After cooling to room temperature, filter and separate the colorless crystalline product, wash it with acetone 2 to 3 times, and dry it at 65°C to synthesize the H2S regenerable adsorption material.
[0031] The synthetic H2S regenerable adsorbent material is molded, and the molding method includes the following steps: a. Take the polyvinyl alcohol solid, dissolve it in 100 mL of hot water, and stir until it becomes a transparent liquid to prepare a polyvinyl alcohol solution.
[0032] b. Mix the synthesized H2S regenerable adsorbent material with methyl cellulose solid, add it into 0.5% polyvinyl alcohol solution, and mix and stir.
[0033] c. Put the mixture with the binder into an extruder for extrusion molding. Then, dry the extruded material at room temperature for 8 hours and then dry it in an oven at 105°C for 3 hours to obtain a molded adsorption material.
[0034] The adsorption-desorption performance of the formed adsorption material is evaluated. The evaluation device for evaluating the regenerable H2S adsorption material has the following structure: it includes an adsorption device and a desorption device connected to the same stainless steel measuring tube 8, the adsorption device includes a compressed air filter 1, the first pipeline L1 of the compressed air filter 1 is connected to the inlet of the drying tower 7, the outlet of the drying tower 7 is connected to the poison gas cylinder 6 through the third pipeline L3, the third pipeline L3 is connected to the first orifice flowmeter 10, and the poison gas cylinder 6 is connected to an inlet of the mixing ball 5; The second pipeline L2 of the compressed air filter 1 is connected to the humidity regulator 2, and multiple groups of humidity regulators 2 are connected in parallel. The humidity regulator 2 is connected to another inlet of the mixing ball 5 through the fourth pipeline L4, and the fourth pipeline L4 is connected to the dry-bulb thermometer 3 and the second orifice flowmeter 4 in sequence; the outlet of the mixing ball 5 is connected to the inlet of the stainless steel measuring tube 8 through the fifth pipeline L5, and the fifth pipeline L5 is connected to the third orifice flowmeter 11. The stainless steel measuring tube 8 is filled with molded adsorption material, and the outlet of the stainless steel measuring tube 8 is connected to the indicator box 9; The desorption device includes a stainless steel measuring tube 8 disposed in a water bath 12 , with both ends of the stainless steel measuring tube 8 connected to an air generator 13 and a vacuum pump 14 respectively, and a mass flow meter 15 is installed on the pipeline connecting the stainless steel measuring tube 8 and the air generator 13 .
[0035] The evaluation method is carried out in a fume hood using the above evaluation device. The evaluator wears a gas mask and relies on the principle of pressure swing adsorption and temperature swing adsorption, including the following steps: a. Place the formed adsorbent material in the stainless steel measuring tube 8 of the adsorption device, and perform adsorption treatment on the adsorbent material, that is, the adsorbate enters the stainless steel measuring tube filled with the adsorbent, and is adsorbed at room temperature and pressure. When the indicator in the indicator box 9 changes color, that is, when it penetrates, the H2S adsorption capacity is recorded and calculated; Specifically include: aa, compressed air enters the humidity regulator 2 from the compressed air filter 1, and after the temperature and flow are monitored by the dry-bulb thermometer 3 and the second orifice flowmeter 4, it enters the mixing ball 5 and mixes with the H2S in the poison gas cylinder 6 that enters the mixing ball 5.
[0036] ab, the mixed poison gas enters the stainless steel measuring tube 8 from the mixing ball 5 and passes through the adsorption material.
[0037] ac, the contamination progress is judged by the color change of the indicator in the indicator box 9 connected to the rear of the stainless steel measuring tube 8. When the indicator in the indicator box 9 changes color, that is, when it penetrates, the flow rate is recorded by the third orifice flowmeter 11 installed between the mixing ball 5 and the stainless steel measuring tube 8, and the H2S adsorption capacity is calculated based on the flow rate and time.
[0038] b. When the poison changes the color of the indicator in the indicator box 9, that is, the poison penetrates the adsorbent material, remove the stainless steel measuring tube 8.
[0039] c. Connect the stainless steel measuring tube 8 to the desorption device, connect the air generator 13 and the vacuum pump 14 to the two sides of the stainless steel measuring tube 8 respectively, place the stainless steel measuring tube 8 in a water bath at 60℃~70℃, and introduce air at a flow rate of 200mL / min into the stainless steel measuring tube 8 to vacuum desorb the adsorbent material. At the same time, clean hot air is blown for desorption, so that H2S in the formed adsorbent material is removed from the system to achieve the purpose of regeneration. The desorption time is the same as the adsorption time, and the desorption test is carried out.
[0040] d. After desorption, the stainless steel measuring tube 8 was placed in the evaluation device for adsorption, and evaluation steps a to c were repeated for 5 cycles to verify the reproducibility of the material. The evaluation results are shown below. Figure 3 shown.
[0041] The experimental results show that the regenerative adsorption material prepared and formed by this method can achieve regenerative adsorption of H2S, and the regeneration effect is stable.
[0042] The scope of protection claimed by the present invention is not limited to the above specific embodiments. For those skilled in the art, the present invention may have various deformations and changes. Any modifications, improvements and equivalent substitutions made within the concept and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a regenerable H2S adsorbing material, characterized in that: The following steps are involved: a. Take 0.06-0.08 mmol of scandium trifluoride solid and 0.010-0.03 g of biphenyltetracarboxylic acid, add 4.0-5.0 mL of tetrahydrofuran solution, 3.0-5.0 mL of N,N-dimethylformamide solution, 1.0-2.0 ml of water, and 2-3 drops of 36.5% hydrochloric acid, and perform ultrasonication for 15 minutes to disperse the mixture solution uniformly to obtain a mixed solution; b, reacting the mixture at 75°C for 72 hours; c. After cooling to room temperature, filter and separate the colorless crystalline product, wash it with acetone 2 to 3 times, and dry it at 65°C to synthesize the H2S regenerable adsorption material.
2. The method for preparing a regenerable H2S adsorbing material according to claim 1, characterized in that: In steps a and b, the mixed solution is placed in a polytetrafluoroethylene hydrothermal reactor.
3. A method for forming a regenerable H2S adsorbing material, characterized in that: The following steps are involved: a. Dissolve the binder in water to prepare a binder solution; b. Mix the synthesized H2S regenerable adsorbent material with methyl cellulose solid, add it into 0.5% binder solution, and mix and stir; c. Put the mixture with the binder into an extruder for extrusion molding. Then, dry the extruded material at room temperature for 8 hours and then dry it in an oven at 105° C. for 3 hours to obtain a molded adsorption material.
4. The method for forming a regenerable H2S adsorbing material according to claim 3, characterized in that: The binder is polyvinyl alcohol solid; in step a, the polyvinyl alcohol solid is dissolved in 100 mL of hot water and stirred until a transparent liquid is present to prepare a polyvinyl alcohol solution.
5. A method for evaluating a regenerable H2S adsorbing material, characterized in that: The structure of the evaluation device for evaluating regenerable H2S adsorbing materials is as follows: it comprises an adsorption device and a desorption device connected to the same stainless steel measuring tube (8), the adsorption device comprises a compressed air filter (1), a first pipeline (L1) of the compressed air filter (1) is connected to the inlet of a drying tower (7), the outlet of the drying tower (7) is connected to a poison gas cylinder (6) via a third pipeline (L3), and the poison gas cylinder (6) is connected to an inlet of a mixing ball (5); The second pipeline (L2) of the compressed air filter (1) is connected to the humidity regulator (2), and the humidity regulator (2) is connected to another inlet of the mixing ball (5) through the fourth pipeline (L4); the outlet of the mixing ball (5) is connected to the inlet of a stainless steel measuring tube (8) through a fifth pipeline (L5), the stainless steel measuring tube (8) is filled with a molded adsorption material, and the outlet of the stainless steel measuring tube (8) is connected to an indicator box (9); The desorption device comprises a stainless steel measuring tube (8) arranged in a water bath (12), the two ends of the stainless steel measuring tube (8) being respectively connected to an air generator (13) and a vacuum pump (14), and a mass flow meter (15) being installed on the pipeline connecting the stainless steel measuring tube (8) and the air generator (13); The evaluation method includes the following steps: a. placing the formed adsorbent material in a stainless steel measuring tube (8) of an adsorption device, subjecting the adsorbent material to adsorption treatment, and recording and calculating the H2S adsorption capacity when the indicator in the indicator box (9) changes color; b. When the poison causes the indicator in the indicator box (9) to change color, that is, the poison penetrates the adsorbent material, the stainless steel measuring tube (8) is removed; c. Connect the stainless steel measuring tube (8) to the desorption device, connect an air generator (13) and a vacuum pump (14) to both sides of the stainless steel measuring tube (8), respectively, place the stainless steel measuring tube (8) in a water bath at 60°C to 70°C, introduce air at a flow rate of 200 mL / min into the stainless steel measuring tube (8), desorb the adsorbent material by vacuum pumping, and simultaneously desorb by clean hot air blowing, and the desorption time is the same as the adsorption time; d. After desorption is completed, the stainless steel measuring tube (8) is placed in the evaluation device for adsorption, and evaluation steps a to c are repeated.
6. The method for evaluating a regenerable H2S adsorbing material according to claim 5, characterized in that: Step a The following steps are involved: aa, compressed air enters the humidity regulator (2) from the compressed air filter (1), passes through the dry-bulb thermometer (3) and the second orifice plate flowmeter (4) to monitor the temperature and flow, and then enters the mixing ball (5) to mix with the H2S in the poison gas cylinder (6) entering the mixing ball (5); ab, the mixed poison gas enters the stainless steel measuring tube (8) from the mixing ball (5) and passes through the adsorption material; ac, the progress of the contamination is determined by the color change of the indicator in the indicator box (9) connected to the rear of the stainless steel measuring tube (8), the flow rate is recorded by a third orifice flow meter (11) installed between the mixing ball (5) and the stainless steel measuring tube (8), and the H2S adsorption capacity is calculated based on the flow rate and time.
7. The method for evaluating a regenerable H2S adsorbing material according to claim 5, characterized in that: The third pipeline (L3) is connected to a first orifice flowmeter (10), the fourth pipeline (L4) is connected in sequence to a dry-bulb thermometer (3) and a second orifice flowmeter (4), and the fifth pipeline (L5) is connected to a third orifice flowmeter (11).
8. The method for evaluating a regenerable H2S adsorbing material according to claim 5, characterized in that: The humidity regulators (2) are connected in multiple groups in parallel.